Analisis Hukum terhadap Pelaku Kekerasan Seksual yang Dilakukan Anak Sebagai Pelaku terhadap Anak sebagai Korban (Studi Putusan Nomor: 18/Pid.Sus-Anak/2020/Pn. Sbs.) - Dandy Leonardus Tarigan; Venia Utami Keliat (Verdict: Journal of Law Science, 2026)
Sexual violence involving children as both perpetrators and victims presents a complex legal issue because it requires balancing victim protection with the rehabilitation of child offenders. This study aims to examine the legal regulation of sanctions for sexual violence under Indonesian child protection law and to analyze the judicial reasoning in Decision Number 18/Pid.Sus-Anak/2020/PN.Sbs. The research employs a normative legal method using statutory and case approaches. Primary legal materials consist of legislation on child protection, the juvenile criminal justice system, the Criminal Code, and the selected court decision, supported by secondary and tertiary legal materials. Data were analyzed qualitatively through legal interpretation and deductive legal reasoning. The findings indicate that Indonesian law distinguishes sanctions for adult and juvenile offenders. Adult perpetrators are subject to imprisonment of five to fifteen years and fines of up to IDR 5 billion under the Child Protection Law. In contrast, juvenile offenders are sentenced under the Juvenile Criminal Justice System, which emphasizes restorative justice, rehabilitation, diversion, and reduced sentencing. In Decision Number 18/Pid.Sus-Anak/2020/PN.Sbs, the court found that all elements of the offense had been proven and imposed a sentence of ten months’ imprisonment and six months of vocational training after considering the offender’s age, the psychological impact on the victim, and the principles of justice, legal certainty, and child protection. The study concludes that judicial decisions involving juvenile sexual offenders should maintain a balance between accountability, victim protection, and the best interests of the child.